Prácticas culturales para el manejo de la Sigatoka negra en bananos y plátanos - Orozco-Santos, Mario; Orozco-Romero, Jose; Perez-Zamora, Octavio; Manzo-Sanchez, Gilberto; Farias-Larios, Javier; Moraes, Wilson da Silva [UNESP] (Soc Brasileira Fitopathologia, 2008)
Black sigatoka (Mycosphaerella fijiensis) control consists in the continuous use of fungicide sprays and cultural practices. Cultural control reduces inoculum sources of the pathogen and favorable environmental conditions for its development, as well as it increases the vigor of the plants. In order to manage the disease it is necessary to know its behavior through the time, its relationship with the weather and the crop management. The most important cultural practice to reduce the inoculum source is the removal of the whole affected leaves or only the diseased portions of the leaves. The removed tissue is placed over the ground and the use of urea is feasible to accelerate its decomposition. An alternative practice is the mini-composting that consists in forming small heaps with the dead leaves and harvested plants for its quick degradation, which allows to reduce the pathogen inoculum and to incorporate nutrients and organic matters into the soil. The early pruning of the tips of the young leaves before they show symptoms of the disease and the quick elimination of harvested plants reduce the inoculum. Also, the agronomic management of the crop helps to reduce the favorable conditions and to increase the vigor of the plants: this management considers plantation density, drainage systems, irrigation methods, control of weeds, chemical-biological fertilization, and nematode control. Copyright by the Brazilian Phytopathological Society.

El control de la Sigatoka negra (Mycosphaerella fijiensis) se basa en el uso continuo de fungicidas y prácticas de cultivo. El control cultural reduce las fuentes de inóculo del patógeno y las condiciones favorables para su desarrollo, así como incrementa el vigor de las plantas. Para combatir la enfermedad se requiere conocer su comportamiento a través del tiempo, su relación con el clima y las prácticas de manejo. La práctica más importante para reducir la fuente de inóculo es la remoción de hojas afectadas o porciones de éstas. El tejido removido se deposita en el suelo y es factible la aplicación de urea para acelerar su descomposición. Una práctica alternativa es el "minicomposteo", que consiste en colocar la hojarasca y plantas cosechadas en pequeños montones para su rápida degradación, lo cual reduce el inóculo e incorpora nutrientes y materia orgánica al suelo. La poda temprana de las puntas de hojas jóvenes (antes de presentar lesiones esporuladas) y la eliminación rápida de plantas cosechadas disminuyen el inóculo. También, el manejo agronómico del cultivo como densidad de plantación, sistemas de drenaje, métodos de riego, control de malezas, fertilización química-biológica y control de nematodos, ayuda a reducir las condiciones favorables para el desarrollo de Sigatoka negra e incrementar el vigor de las plantas.
Cultural practices for the management of black sigatoka in bananas and plantains
Keywords: Cultural control; Mycospharerella fijiensis